The impact of IL-10 gene polymorphism 1082A/G (rs1800896) on increased IL-10 secretion in patients with chronic kidney disease in the Kurdistan Region of Iraq // Impacto del polimorfismo 1082A/G (rs1800896) del gen de IL-10 sobre la secreción de IL-10 en pacientes con enfermedad renal crónica en la región Kurdistán de Irak - Azeez, Sarhang H.; Darogha, Suhaila N. (Investigación Clínica, 2020)
Abstract Studies have indicated that interleukin-10 gene polymorphism at 1082A/G is associated with chronic kidney disease (CKD). The aim of this study was to determine Il-10 gene polymorphism in CKD patients and identify the risk factors and prevalence of the disease among Kurdish patients. It was also aimed at finding out the serum levels of IL-10 in different genotypes, AA, GA and GG. The study included 108 patients with CKD: 54 on hemodialysis (HD) and 54 renal-transplanted (RT) and 54 healthy subjects. The mean age for HD, RT and healthy subjects was respectively 46.1, 36.8 and 40.2. Half of the HD patients and healthy subjects (50%) were male and half were female, while 55.6% of the RT patients were male and 44.4% female. According to the allele frequency of both G and A, there was no significant difference between both groups of patients and the healthy subjects (P=0.42). The AG genotype was independently associated with increased risk of CKD undergoing HD and RT, while the GG genotype showed an increased risk for renal failure. The levels of serum IL-10 concentrations increased significantly in both groups of patients compared to the healthy subjects. Regarding the genotypes, the genotype AA had the highest concentration among the patients, while a high level was found in genotype GA in the healthy subjects. The lowest level of this cytokine was found in both genotypes GG and AA in the healthy subjects. The findings of the present study revealed that IL-10 gene polymorphism at 1082 A/G (rs1800896) and increased concentration of serum IL-10 were associated with increasing chronic kidney disease in the Iraqi Kurdish population. Resumen Varios estudios han indicado que el polimorfismo 1082A/G (rs1800896) del gen de IL-10 está asociado con la enfermedad renal crónica (ERC). El propósito de este estudio fue determinar el polimorfismo del gen de la IL-10 en pacientes con ERC e identificar los factores de riesgo y prevalencia de la enfermedad entre pacientes Kurdos. También se determinaron las concentraciones séricas de IL-10 en los diferentes genotipos AA, GA y GG presentes. El estudio incluyó 108 pacientes con ERC: 54 en hemodiálisis (HD) y 54 con trasplante renal (TR) y en 54 sujetos sanos. Las edades promedio para los HD, TR y sujetos sanos fueron 46,1, 36,8 y 40,2 años, respectivamente. La mitad de los pacientes en HD y de los sujetos sanos eran hombres y la otra mitad eran mujeres, mientras que el 55,6% de los pacientes con TR eran hombres y 44,4 % eran mujeres. Considerando la frecuencia de los alelos G y A, no hubo diferencias estadísticamente significativas entre ambos grupos de pacientes y los sujetos sanos (p= 0,42). El genotipo AG se encontró independientemente asociado con un riesgo aumentado de pacientes con ERC bajo HD y TR, mientras que el genotipo GG mostró un riesgo mayor de falla renal. Las concentraciones séricas de IL-10 se encontraron aumentadas significativamente en ambos grupos de pacientes, comparadas con las de los sujetos sanos. En consideración a los genotipos, el genotipo AA tenía las más altas concentraciones entre los pacientes, mientras que se encontró un mayor nivel en el genotipo GA en los sujetos sanos. Las concentraciones más bajas de esta citocina se encontraron en los genotipos GG y AA de los sujetos sanos. Los hallazgos del presente estudio revelaron que el polimorfismo 1082A/G (rs1800896) del gen de la IL-10 y las concentraciones séricas aumentadas de IL-10 estaban asociadas con aumentos de la enfermedad renal crónica en la población Kurda de Iraq.